Peningkatan Hasil Belajar melalui Palem Materi Tugas dan Wewenang Lembaga Negara Peserta Didik Kelas IX MTsN 3 Demak - Ahmadun Ahmadun (Balai Diklat Keagamaan Semarang, 2022)
The purpose of this study was to obtain a series of information about the process of PPKn learning outcomes which included: 1) the implementation of the use of palm media for students in class IX-1 MTs Negeri 3 Demak, 2) the role of palm media in increasing Civics learning activities for class IX-1 MTs Negeri 3 Demak. , and 3) improving Civics learning outcomes through palm media for class IX-1 students at MTs Negeri 3 Demak.This type of classroom action research is carried out in two (2) cycles. The research subjects were 36 students of class IX-1 MTs Negeri 3 Demak. The data collected were observation sheets for teacher and student activities, learning outcomes data with objective tests and responses from students on palm media using a questionnaire sheet. The classical success indicator is 85% of the student learning outcomes test reaches a score of 75. In accordance with the KKM with a good indicator of success if it reaches 80%. Meanwhile, for teacher activities, the success indicator is said to be successful if it reaches the very good category. The results showed that 1) the learning carried out by the teacher went well, 2) the observation of student activities for affective assessment increased and had met the KKM. 3) Students' responses to palm media in PPKn learning are not saturated, and it is easy to understand the material. Keywords: Learning outcomes, palem media, and the duties and authorities of state institutions